Designing a robust controller for a lower limb exoskeleton to treat an individual with crouch gait pattern in the presence of actuator saturation. (July 2022) - Khamar, Maryam; Edrisi, Mehdi; Forghany, Saeed
Abstract: Crouch gait is a gait anomaly observed in youngsters with cerebral palsy (CP). Rehabilitation robots are useful for treating individuals with crouch gait. Multiple factors have impact on crouch, including contracture, spasticity, weak motor control, and muscle feebleness, which make the designing and controlling of these exoskeletons for this population a challenging job. A harsh kinematic trajectory enforced by an exoskeleton control strategy may place individuals with spasticity at a high risk of muscle tissue injury. Therefore, in this article, a multi-input multi-output (MIMO) control method is proposed to reduce this risk and improve crouch gait pattern. A constrained control law is used in the model since high power demands may threaten the wearer. In addition, the controller needs to be robust enough against external disturbances and uncertainties. Thus, a nonlinear disturbance observer (NDO) is presented to compute the wearer-generated muscular torque and the uncertainties in the modeling. In addition, a robust constrained MIMO backstepping sliding controller (CMBSC) based on NDO is used to deal with the effect of actuator saturation and uncertainties. A simulation test was used to validate the proposed model and controller. The results of Simulation confirmed the efficiency of the proposed control method when applied to crouch gait with subject specific gait reference. Then, some experimental tests were undertaken to validate the efficiency of the proposed controller. Highlights: Considering the human muscular effort and uncertainties of parameters in modeling of a lower limb exoskeleton in proposed controller. Designing multi input multi output MIMO disturbance observer and backstepping sliding controller to eliminate the stiffness of the human body and uncertainties of the structure. The disturbance observer is used to estimate the exerted human torque and its uncertainties then they are used in controller design in order to utilize less power when it is in favor of the motion and eliminate those when they are against. The actuator saturation is considered and its stability is proved, thus the model is more realistic now. Evaluating control strategies by OpenSim and MATLAB interface and demonstrate the effectiveness of the proposed control method by applying to a crouch gait pattern before performing the experimental test to reduce challenges. Some experimental results are added to support the idea.